PAREWA SEBAGAI PROFIL SENIMAN TRADISI MINANGKABAU - S., Syahrial (Institut Seni Indonesia Surakarta, 2015)
This paper will discuss one of the traditional Minangkabau community groups namelyParewa class as the profile of traditional artists. The author will explain about the â€œartist profiletraditionâ€ and its relationship with the arts, particularly dance (Minangkabau traditional dance).To uncover these problems, the authors use qualitative methods and techniques of data collectionby observation, interview, and literature study. Furthermore, perform data analysis, verification,and conclude. The result of observation and discussion shows that Parewa is a class of people whohave a good martial arts skills and an expert in the art. This can be seen in the movements of thedance, which is dominated by movements of martial arts with agile character, sharp and definite.The conclusion is Parewa is a class of traditional community in Minangkabau that very intensively involve in the arts, it is seen on every activity in the life of society such as traditionalceremonies. This involvement is not just attending traditional ceremonies that there was onlyart, but also involved as a perpetrator of the arts.Keywords: Parewa, Profile, Pencak Silat.